2008
DOI: 10.1203/pdr.0b013e31815ef71c
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Reverses Hypoxic Pulmonary Hypertension in Highland and Lowland Newborn Sheep

Abstract: Perinatal exposure to chronic hypoxia induces sustained hypertension and structural and functional changes in the pulmonary vascular bed. We hypothesized that highland newborn lambs (HLNB, 3600 m) have a higher pulmonary arterial pressure (PAP) due in part to a higher activity/expression of phosphodiesterase 5 (PDE5). We administered sildenafil, a PDE5 inhibitor, during basal and hypoxic conditions in the pulmonary hypertensive HLNB and compared them to lowland newborn lambs (LLNB, 580 m). Additionally, we com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 42 publications
8
59
0
2
Order By: Relevance
“…This condition may partially compensate the marked pulmonary vasoconstriction observed in these lambs. All these observations are in agreement with our previously published work (14,16). Support for our in vivo results concerning the 2-APB inhibition of hypoxic pulmonary vasoconstriction comes from studies showing the abolition by 2-APB of calcium influx in cultured pulmonary artery myocytes stimulated with hypoxia Values are the means Ϯ SE for heart rate (HR), systemic arterial pressure (SAP), and systemic vascular resistance (SVR) The cardiovascular variables were recorded and calculated during preinfusion (Basal), during infusion with vehicle or 2-APB (BasalϩInfusion), during acute hypoxia and during recovery.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This condition may partially compensate the marked pulmonary vasoconstriction observed in these lambs. All these observations are in agreement with our previously published work (14,16). Support for our in vivo results concerning the 2-APB inhibition of hypoxic pulmonary vasoconstriction comes from studies showing the abolition by 2-APB of calcium influx in cultured pulmonary artery myocytes stimulated with hypoxia Values are the means Ϯ SE for heart rate (HR), systemic arterial pressure (SAP), and systemic vascular resistance (SVR) The cardiovascular variables were recorded and calculated during preinfusion (Basal), during infusion with vehicle or 2-APB (BasalϩInfusion), during acute hypoxia and during recovery.…”
Section: Discussionsupporting
confidence: 94%
“…According to previous studies (16,18), we observed the thickening of pulmonary artery medial layer in our hypertensive HA lambs. Nevertheless, further experiments are needed to establish whether there is a cause-effect relationship between enhanced SOC function and pulmonary arterial remodeling in the hypoxic newborn sheep.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In the ovine newborn from HA, the vascular reactivity is elevated compared to sea level counterpart [67,74]. The imbalance in the cGMP signaling, favors the vasoconstriction.…”
Section: Perinatal Cardiovascular Responses and Treatmentmentioning
confidence: 99%